PERTUMBUHAN DAN HASIL 3 VARIETAS PADI (Oryza sativa L.) DENGAN BERBAGAI DOSIS PUPUK HAYATI DI LAHAN RAWA LEBAK - Mahdiannoor Mahdiannoor; Nurul Istiqomah; Maulina Hasanah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2018)
Paddy (Oryza sativa L.) is a commodity that is widely cultivated by the people of Hulu Sungai Utara, because the area is in the low land in the form of lebak swamps. Generally cultivated rice varieties that have early maturity. The use of various new superior rice varieties is one way to increase rice productivity in addition to fertilization. By giving various doses of biofertilizer, it is expected to increase rice productivity. This study aims to determine (i) the effect of the interaction of varieties and biofertilizers, (ii) the influence of rice varieties (iii) the effect of biofertilizers, (iv) the best interaction of rice varieties and biofertilizer (v) the best rice varieties and (vi) the best dosage of biofertilizers for the growth and yield of rice plants in swampy swamps. Using a Randomized Factor Two-factor factorial group. The first factor was 3 varieties of rice (V) and the second factor was the administration of biofertilizers (P) with 5 doses. The results showed that there was an effect of rice variety interaction on the number of tillers aged 27 HST, obtained the best varieties of v1 treatment (Inpari 17 varieties) and biofertilizers at p0 treatment affected the number of tillers aged 37 HST in lebak swamps.